The effect of oxytocin, sublingual, and intrauterine misoprostol on blood loss in cesarean delivery: A randomized clinical trial - Mahdieh Masoumzadeh; Vahideh Rahmani; Manizheh Sayyah-Melli; Anis Sani (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background: The efficacy of different uterotonic agents is yet to be determined. Methods: This was a randomized clinical trial on 240 pregnant mothers with a history of cesarean section in three groups: A: sublingual misoprostol and oxytocin, B: intrauterine misoprostol and oxytocin, and C: a higher dose of oxytocin alone. The intrapartum blood loss and the estimated blood loss within 24 h after surgery were compared between the groups. Results: The baseline characteristics showed no significant differences among the groups. The volume of blood loss during surgery and within 24 h postpartum did not differ significantly among the groups (A: 230.72 ± 97.30, B: 245.60 ± 88.50, C: 229.02 ± 109.78, p = 0.115, and A: 2023.84 ± 480.08, B: 2045.26 ± 598.99, C: 2025.61 ± 538.93, p = 0.819, respectively). Conclusion: Intrauterine misoprostol plus oxytocin, sublingual misoprostol plus oxytocin and a higher dose of oxytocin did not show any significant difference in the amount of blood loss during surgery and within 24 h post-operation.